Future prospects for gene delivery systems - SEZER, ALİ DEMİR (TAYLOR & FRANCIS LTD, 2017)
Introduction: Gene therapy is the challenging area of biotechnology. Despite its promise for critical diseases, it has serious safety and efficiency issues, particularly with regards to gene transfer systems. Areas covered: We examined the current situation with gene transfer systems and addressed problems this technology. We then searched patent applications about in the area from the Patentscope online system, the international patent database. We analyzed the data obtained to get a general idea about gene delivery systems designed for future use and assessed approaches for more efficient, safer and valid delivery systems. Expert opinion: When quality assurance terms are fulfilled, some of these issues (genetic changes, mutations) could be minimized during the production process. Modification of vectors for improving their efficiency and safety or development of alternative transfer systems could be the solutions for these problems. Gene transfer technologies are important for gene therapy and should demonstrate effective, target-specific and acceptable safety profiles. For this reason, searching for alternatives to current systems is a necessity.
Keywords: Gene therapy; gene delivery systems; gene transfer; gene patents; CLINICAL-TRIALS WORLDWIDE; IMMUNE-RESPONSES; VIRAL VECTORS; THERAPY; PROGRESS; UPDATE; EXPRESSION; ELEMENTS; CELLS